Wasiilah Google Sites Fii tadriis Maharah Al-Qira’ah As Samitha Fii Al-Madrasah Al-Aliyah Al-Hukumiyah 2 Kuantan Singingi - Aisah Aisah (Universitas Islam Negeri Imam bonjol Padang, 2022)
The main problem in this research is “does media Google Sites influence in learning silent reading skills on student eleventh graders of Madrasah Aliyah Negeri 2 Kuantan Singingi?”. This research is very broad, the author limits the first is the ability to silent reading skills before using media Google Sites. second is the using of media Google Sites in learning silent reading skills. third is the influence of media Google Sites in learning silent reading skills. The aims of this research is to describe ability silent reading skills before using media Goole Sites, to describe using media Google Sites, to describe influence media Google Sites in improving ability silent reading skills on student eleventh graders. The research method used is quantitative study approach that is quasi eksperimen mothod and analytic data use SPSS. The result in this research is first the ability before use media Google Sites in control class is 69, and eksperimental class is 68,33. second is the using media Google Sites in three steps. first is opening, second is mian activity its five steps observing, asking, trying, associating, and communicating, third is closing. third is the influence media Google Sites in eksperimental class is 81,66 and control class is 71,33. and based on result of Paired Sample T test, T table 3,460 bigger than T count 2,043. and sig(2-Tailed) 0,005 bigger than 0,000. its mean Median oogle Sites is influence to ability silent reading skills on student eleventh graders of Madrasah Aliyah Negeri 2 Kuantan Singingi